Efektivitas Metformin dalam Meningkatkan Kehamilan Klinis dan Angka Kelahiran Hidup pada Wanita dengan PCOS: Tinjauan Naratif dengan Implikasi bagi Kesehatan Masyarakat - Juwana Janu; Reny Haryani (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Infertility due to ovulatory disorders presents a significant challenge in reproductive health, with Polycystic Ovary Syndrome (PCOS) being one of the leading causes. Metformin has been widely used in clinical practice to manage ovulatory dysfunction in women with PCOS, either as monotherapy or in combination with other therapeutic approaches. This narrative review aims to evaluate the effectiveness of metformin on clinical pregnancy rate (CPR) and live birth rate (LBR) through a critical appraisal of nine scientific publications published in the past ten years. Relevant literature was gathered through the PubMed database using selected keywords and screened based on predefined inclusion and exclusion criteria. Findings indicate that metformin provides beneficial effects on improving CPR, particularly when used as an adjunct therapy prior to IVF protocols or in combination with non-pharmacological approaches such as acupuncture. However, evidence related to LBR demonstrates greater variability. Overall, these findings support the role of metformin as part of an individualized, evidence-based fertility treatment strategy. This review offers important clinical implications for optimizing infertility management in women with PCOS.